Diamond/Porous Titanium Nitride Electrodes With Superior Electrochemical Performance for Neural Interfacing - Meijs, Suzan; McDonald, Matthew; Sørensen, Søren; Rechendorff, Kristian; Fekete, Ladislav; Klimša, Ladislav; Petrák, Václav; Rijkhoff, Nico; Taylor, Andrew; Nesládek, Miloš; Pennisi, Cristian P. (Frontiers in Bioengineering and Biotechnology, 2018)
Robust devices for chronic neural stimulation demand electrode materials which exhibit high charge injection capacity and long-term stability. Boron-doped diamond (BDD) electrodes have shown promise for neural stimulation applications, but their practical applications remain limited due to the poor charge transfer capability of diamond. In this work, we present an attractive approach to produce BDD electrodes with exceptionally high surface area using porous titanium nitride (TiN) as interlayer template. The TiN deposition parameters were systematically varied to fabricate a range of porous electrodes, which were subsequently coated by a BDD thin-film. The electrodes were investigated by surface analysis methods and electrochemical techniques before and after BDD deposition. Cyclic voltammetry measurements showed a wide potential window in saline solution (between -1.3 V and 1.2 V vs. Ag/AgCl). Electrodes with the highest thickness and porosity exhibited the lowest impedance magnitude and a charge storage capacitance of 253 mC/cm2, which largely exceeds the values previously reported for porous BDD electrodes. Electrodes with relatively thinner and less porous coatings displayed the highest pulsing capacitances, which would be more favorable for stimulation applications. Although BDD/TiN electrodes displayed a higher impedance magnitude and a lower pulsing capacitance as compared to the bare TiN electrodes, the wider potential window likely allows for higher charge injection without reaching unsafe potentials. The remarkable reduction in the impedance and improvement in the charge transfer capacity, together with the known properties of BDD films, makes this type of coating as an ideal candidate for development of reliable devices for chronic neural interfacing.